PENELUSURAN SEJARAH AL-QUR’AN VERSI ORIENTALIS: SEBUAH GAMBARAN METODOLOGIS - Madyan, Ahmad Shams (IAIN Kediri, 2015)
Although being defined as a scholarly knowledge of Eastern cultures and languages, Orientalism seemed to beÃ‚Â confined to a mere discussion on Islam. OrientalistÃ¢â‚¬â„¢s hostorical approaches toward the QurÃ¢â‚¬â„¢an have raised heatedÃ‚Â debates among Muslims. As an approach, Orientalism is not a free value, rather it containes ideology-basedÃ‚Â accounts despite of its alledgedly scientific nature. This paper attempts to answer whether or not OrientalismÃ¢â‚¬â„¢sÃ‚Â historical method of interpreting the QurÃ¢â‚¬â„¢an is really scientific or it needs to be countered and criticized.Keywords: Orientalisme, al-QurÃ¢â‚¬â„¢an, Autentisitas